Hubungan Suntik Kb 3 Bulan Terhadap Kelancaran Menyusui Di Bpm Perawati Desa Karya Teladan Kabupaten Musi Rawas Sumatera Selatan - Sulastri, Mepi; Umami, Desi Aulia; Resmi, Ermi (Universitas Dehasen Bengkulu, 2025)
The use of birth control according to the type of contraceptive device or method in Indonesia is dominated by the use of injectable contraceptives. The problem of non-fluency in breastfeeding is a side effect that often occurs when using 3-month injectable birth control. The results of a survey of 3-month injection contraceptive acceptors who visited BPM Nursing, most of them (80%) experienced breast milk irregularities. The aim of the research was to determine the relationship between 3-month birth control injections and smooth breastfeeding in Bpm Nursei Karya Teladan Village, Musi Rawas Regency, South Sumatra. Cross sectional approach analytical survey research design. The population in this study was 132 3-month injection acceptors. The sample in this study was 57 3-month injection acceptors taken using purposive sampling by selecting the sample size and population according to inclusion and exclusion criteria. The research instrument used a questionnaire. The results of the study showed that more than half (60%) used 3-month injectable contraceptives for >1 year and more than half (68%) experienced difficulties in breastfeeding. The results of the chi-square test analysis p value = 0.010 < α= 0.05 The conclusion is that there is a relationship between 3-month birth control injections and smooth breastfeeding in BPM Nursei Karya Teladan Village, Musi Rawas Regency, South Sumatra.